873 The Keystone Challenge- Volar Displaced Intra-Articular Distal Radius Fractures with Lunate Fossa Fragment. (12th October 2021) - Cheruvu, M S; Dass, D; Ford, D J; Roushdi, I
Abstract: Aim: Volar displaced fractures of the distal radius are unstable and warrant operative management. A subset of patients with volar displaced fractures also has a separate lunate fossa fragment, a specific injury with greater instability that may precipitate carpal subluxation. We aim to review our long-term experience in the management of this complex injury, exploring surgical technique which may improve treatment. Method: We retrospectively reviewed all volar displaced distal radius fixations between 2015 and 2020. Inclusion criteria: any displaced intra-articular volar distal radius fracture with lunate fragment involvement undergoing volar fixation and over 16 years of age. Exclusion criteria: shaft fractures, extra-articular fractures, open fractures, fractures fixed using k-wires or external fixation, revision surgery and patients without follow-up. We adapted our surgical approach in order to address this more complex fracture pattern, and all operations were performed by specialist hand surgeons. Results: 468 distal radius fractures were assessed, of which 29 (6%) cases included a lunate fossa fragment. 20 (69%) of patients were female, mean age was 59 years (SD 12.4). Mean length of stay was 5 hours and mean operative time was 96 mins (range 79-95). No patients had carpal subluxation, fracture fixation failure or return to theatre for any reason. Conclusions: From our experience as a specialist orthopaedic institution, we recommend the extended FCR approach and intra-focal exposure to manage this complex injury. In particular, the lunate fossa fragment is the keystone which requires dedicated reduction prior to tackling the remaining fracture configuration.